Domestic Abuse (Al-AdraÍ‚r) towards Ijebu Muslim Women and Its Implications for Marital Stability and Sustainability in Ijebuland, Ogun State - Egbeolowo, Dauda Ashir (NIU Journal of Humanities, 2020)
Domestic abuse is a global phenomenon which transcends national, cultural, racial, class and religious boundaries. There are three dimensions of it- spousal (a combination of wife and husband abuse), child and elder abuse. Its acts include beating, stabbing, acid bath, outright killing, denial of sex, marital rape, denial of housekeeping allowance, cursing among others. Despite global and local efforts at preventing it through advocacy, law enactment and prosecution, the menace is on the increase. These acts often lead to marital instability in many Muslim homes, especially in Ijebuland. Therefore, this study seeks to identify the acts of domestic abuse ( Al-AdraÍ‚r in Islamic terminology) being experienced by the Ijebu Muslim women, the reason(s) why they are victims of such acts, its implications for their marital stability and way(s) of curbing such societal menace in Ijebuland in particular, and the nation in general. The study adopts the descriptive research design of the survey type. Its target population consists of Ijebu Muslim women in Ijebuland out of which three hundred (300) constitute the sample of the study.  A self-developed questionnaire is an instrument used for data collection. Of the 300 copies of the questionnaire administered at various Jumaâ€™at mosques, 283 copies were properly filled and returned and these were quantitatively analysed. Keywords: Domestic Abuse, ( Al-AdraÍ‚r), Ijebu Muslim women, Ijebuland